Learning from the Past: A Contentious Issue? - Ahmad, Qasim (SUSURGALUR, 2014)
ABSTRACT: Given that history is âman-madeâ and those who study or read history are men and women who carry with them their own respective perspectives and value systems, it is difficult to imagine that people will learn the same lessons from history. This is not to say that one cannot learn from history; one certainly can, but expect not that oneâs view would be broadly shared by others. This article looks at the controversy surrounding the often heard exhortation that one ought to take lessons from history, lest one would succumb to repeating past follies. However, the aptness of trying to learn from history has often been questioned. This skepticism is understandable as it is said that the exercise cannot possibly be free from subjective elements. On the other hand, a persistent doubting or outright denying of the appropriateness of trying to draw lessons from the historical past, could in a way, undermine the very raison dâÃªtre or rationale for studying history itself. While some might be prepared to debunk history as a discipline, others would certainly want to defend its usefulness. In an attempt to shed some light to this seeming quandary, this article proposes that our attention be directed to the âobviousâ lessons that we can glean from the past, contentious though that proposal might be. KEY WORD: History, historical lessons, interpretations, perspectives, value systems, and contentious issue. IKHTISAR: Artikel ini bertajuk âBelajar dari Masa Lalu: Satu Isu Perbalahan?â. Memandangkan bahawa sejarah adalah âbuatan manusiaâ dan mereka yang mengkaji atau membaca sejarah adalah lelaki dan wanita yang membawa bersama perspektif mereka masing-masing dan sistem nilai, ia adalah sukar untuk membayangkan bahawa orang akan belajar mengenai pelajaran yang sama dari sejarah. Ini bukan untuk mengatakan bahawa kita tidak boleh belajar dari sejarah; satu yang pasti boleh, tetapi tidak mengharapkan pandangan seseorang akan dikongsi secara meluas oleh orang lain. Artikel ini meninjau kontroversi yang sering berlegar di sekitar saranan agar kita mengambil pelajaran dari sejarah demi menghindari kesilapan masa silam. Namun begitu, kewajaran gesaan ini sering dipersoalkan. Sikap sangsi ini tidak sukar difahami kerana usaha sedemikian itu dikatakan tidak mungkin telerai dari unsur subjektif. Sebaliknya, tindakan mempersoalkan secara berterusan atau menafikan secara mutlak kecocokan upaya mendapatkan iktibar dari sejarah boleh, dari satu segi, menjejaskan asas pengkajian sejarah itu sendiri. Mungkin sesetengah pihak tidak keberatan untuk mencabar keutuhan sejarah sebagai satu displin, tetapi tentunya ada golongan lain yang mahu membela peranannya. Sebagai satu langkah untuk menghuraikan sedikit-sebanyak dilema yang kelihatan ini, artikel ini mengajak para pembaca memberikan tumpuan kepada pengajaran âjelasâ yang dapat diperolehi dari sejarah, biarpun anjuran itu juga boleh mengundang kontroversi.KATA KUNCI: Sejarah, pelajaran sejarah, tafsiran, perspektif, sistem nilai, dan isu perbalahan.About the Author: Prof. Datoâ Dr. Qasim Ahmad is a Lecturer at the Faculty of Administrative Science and Policy Studies UiTM (Universiti Teknologi MARA), Shah Alam, Selangor Darul Ehsan, Malaysia. E-mail: qasim@salam.uitm.edu.myHow to cite this article? Ahmad, Qasim. (2014). âLearning from the Past: A Contentious Issue?â in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(1), Maret, pp.1-10. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (January 15, 2014); Revised (February 25, 2014); and Published (Maret 24, 2014).